COBIT 5 : enabling processes - Information Systems Audit and Control Association (ISACA).; Information Systems Audit and Control Association (ISACA). (Rolling Meadows, IL. : ISACA, 2012)
COBIT 5: enabling processes complements COBIT 5. It contains a detailed reference guide to the processes that are defined in the COBIT 5 process reference model.
Includes bibliographical references.
oif 04/06/14
Loan
Keywords: COBIT (Information technology management standard).; Information technology; Business enterprises